PENDAMPINGAN MASYARAKAT DALAM PENGELOLAAN DESA WISATA GUNA MENINGKATKAN PENDAPATAN DI DESA TANJUNG SETIA KECAMATAN PESISIR SELATAN KABUPATEN PESISIR BARAT - Khoiruddin Khoiruddin; Iskandar Syukur; Muslim Muslim (Jurnal Abdimas Bina Bangsa, 2023)
The potential of Tanjung Setia village is very supportive for the achievement of tourism village goals. The potential beauty of the sea that can be used for surfers owned by Tanjung Setia village and the hospitality of its residents is a big capital for the development of tourism in the pekon. If all the village potentials owned by Tanjung Setia pekon can be synergized, then the vision of Pesisir Barat Regency to make Tanjung Setia pekon a tourist village will become a reality. But in reality this is not the case. The existing potential is not managed massimally. Tourists from outside the area should come to visit Tanjung Setia beach. That didn't happen. What tourists need when doing tours is widely obtained at Tanjung Setia Beach. People in Tanjung Setia should be able to make ideas, a kind of creative business to attract tourists to visit the local village. Therefore, assistance is needed to the community in managing Tanjung Setia Beach and making Tanjung Setia village a tourist village